Low ectomycorrhizal inoculum potential and diversity from soils in and near ancient forests of bristlecone pine (Pinus longaeva) - Bidartondo,MI; Baar,J; Bruns,TD (Canadian Journal of Botany, 2001)
Intersite variation in ectomycorrhizal (ECM) inoculum potential in soils from 16 sites located in arid subalpine areas of the White Mountains of California was quantified. The study sites included valleys dominated by big sagebrush (Artemisia tridentata Nutt.) and mountainsides dominated by ancient Great Basin bristlecone pine (Pinus longaeva Bailey). ECM inoculum potential was not detected at three of four valley sites nor in 42% of forest soil samples. Only 10 mycorrhizal species were detected in bioassays, and four of those accounted for 94.5% of all colonized seedlings, in order of decreasing abundance these were Pyronemataceae sp., Rhizopogon sp., Wilcoxina rehmii Yang & Korf, and Cenococcum sp. These species were identified also from in situ mycorrhizal roots. The abundance of the dominant Pyronemataceae sp. was significantly positively correlated with pH, which at all forest sites was high compared with typical conifer forest soils. Our results show that the ECM inoculum potential of soils is low, homogeneous, and spatially restricted in these ancient high-elevation forests.